The “Problem” of L2 Writers in College Composition Placement: Identity, Outcomes, and the Future of Directed Self Placement - Vanessa Guida Mesina (Studies in Applied Linguistics & TESOL)
In response to the rapidly growing number of international and multilingual students on U.S. college campuses, many colleges’ first year composition (FYC) courses have expanded to include classes designated for “ESL” or “International” students, with increasing scholarship on the best pedagogical practices for such classes.  Despite increasing scholarship on the best pedagogical practices for such classes, the implications of placing students into them remains “the thorniest of issues” (Crusan, 2011), with mounting debate as to how to measure L2 students’ suitability for either “ESL” or “mainstream” writing classes, as well as the role students should play in labelling themselves “ESL” writers. Directed Self-Placement (DSP) is emerging as a more equitable and anti-racist alternative to test-based placement; however, there are concerns about its suitability for L2 writers specifically (Crusan, 2011; Ferris, 2017). This literature review therefore aims to address two questions: (1) what are the unique challenges of placing L2 writers in FYC courses? Specifically, what are the implications of the identity labelling inherent in placing L2 students in courses designated as “ESL” or for “International Students” with regard to student investment and learning outcomes?  (2) Might DSP offer a viable alternative to traditional L2 placement testing that addresses such implications?